2012
DOI: 10.1098/rstb.2012.0231
|View full text |Cite
|
Sign up to set email alerts
|

Potential consequences of climate change for primary production and fish production in large marine ecosystems

Abstract: Existing methods to predict the effects of climate change on the biomass and production of marine communities are predicated on modelling the interactions and dynamics of individual species, a very challenging approach when interactions and distributions are changing and little is known about the ecological mechanisms driving the responses of many species. An informative parallel approach is to develop size-based methods. These capture the properties of food webs that describe energy flux and production at a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
346
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 345 publications
(373 citation statements)
references
References 59 publications
21
346
1
5
Order By: Relevance
“…Moreover, shifts in the body-mass distributions of populations can be triggered by warming or drought of freshwater ecosystems [17,73,93]. These modifications in the community size structure can relax top-down control causing modifications in primary production [14], secondary production [13], community metabolism and biogeochemical fluxes exceeding the direct consequences of warming [9].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, shifts in the body-mass distributions of populations can be triggered by warming or drought of freshwater ecosystems [17,73,93]. These modifications in the community size structure can relax top-down control causing modifications in primary production [14], secondary production [13], community metabolism and biogeochemical fluxes exceeding the direct consequences of warming [9].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, fish production depends more on primary production than on direct effects of temperature, thus stressing the importance of thermal bottom-up cascades (figure 2) in marine systems. Predicted declines of 30-60% in fish production will impose severe threats on the security of the future food supply [13]. These studies suggest that warming may have complex effects on community-level patterns (figure 1d) that feed back to determine population persistence, with high-trophic-level species being most threatened.…”
Section: Warming and Ecosystem Stabilitymentioning
confidence: 95%
See 2 more Smart Citations
“…This increases the total amount of time an individual spends dispersing and naturally also the exposure to the dispersal mortality. Empirical studies have demonstrated the sensitivity of top predators to even small disturbances [45][46][47], which probably stems from their susceptibility to indirect effects [48]. Disturbances to top predators can have far-reaching consequences owing to their wide-ranging distributions and long generation times, slowing recovery and thereby making their sensitivity even more alarming.…”
Section: Discussionmentioning
confidence: 99%